Kawasan Konservasi Mangrove sebagai Penggerak Ekonomi Masyarakat Desa Budeng Kabupaten Jembrana Bali - Febrianti, Desy; Budiadnyani, I Gusti Ayu; Utari, Siluh Putu Sri Dia; Astiana, Ika; Farida, Iftachul; Samanta, Pinky Natalia; Perceka, Medal Lintas; Panjaitan, Fenny Crista Anastasia; Dewi, Resti Nurmala; Khairunnisa, Anis; Cesrany, Mahaldika (Agrokreatif: Jurnal Ilmiah Pengabdian kepada Masyarakat, 2024)
Budeng Village, located in Jembrana Regency, is home to a significant mangrove conservation area featuring 32 species of mangroves with substantial potential for utilization. Conservation activities in this region are led by the Wana Merta Group, which aims to engage the local community of Budeng Village in these deeds. However, the residents have yet to show much interest due to the lack of perceived economic benefits from conservation activities. The purpose of the community service activities conducted in Budeng Village is to enhance the knowledge and skills of the community in transforming mangroves into economically valuable enterprises. These activities comprised three stages: technical guidance, training sessions, and questionnaire distribution. The activities were attended by 15 participants from the Wana Mertha Forest Farmer Group (KTH), which manages the mangrove conservation area in Budeng Village. The technical guidance included institutional strengthening materials for the group. The training sessions covered topics such as mangrove product diversification, processing Brugueira sp. into mangrove chips, processing Xylocarpus granatum into scrubs, processing shrimp and fish into siomay, as well as packaging and digital marketing to support the group's business endeavors. Throughout the technical guidance and training, participants actively engaged in discussions and followed the sessions diligently. The questionnaire results indicated a significant increase in participants' knowledge, from 40% to 73.76%, reflecting an improvement of 34.67% after the activities.